DETERMINATION OF TILT AND AZIMUTH ANGLES OF SOLAR PANELS AT TANJUNGPURA UNIVERSITY SOLAR POWER PLANT USING PVSYST 7.3 SOFTWARE SIMULATION - Muhammad, Dustin; Hiendro, Ayong; Yandri, Yandri (Telecommunications, Computers, and Electricals Engineering Journal (TELECTRICAL), 2024)
Solar Power Plant is a plant that uses solar energy as a renewable source and converts solar energy into electrical energy. To maximize the intensity of sunlight, solar panels need an optimal tilt angle to receive high sunlight intensity. This research aims to determine the optimal tilt angle of solar panels and azimuthal angle so that solar panels obtain maximum output energy. The type of solar panel used is the monocrystalline type with an installed power of 1.51 MW with a total of 2800 panels using a nominal panel power of 540 Wp and 12 units of 1.1 kW inverters. At the research location, Tanjungpura University Solar Power Plant with coordinates 0 °3'37.486" LU 109 °20'34.633" BT (-0.060410, 109.342969). With a simulation method using PVsyst software to determine the optimal tilt angle and solar radiation data on meteonorm 8.1 in PVsyst software. The results showed that the optimal panel tilt angle and azimuth angle in producing maximum output energy at Tanjungpura University Solar Power Plant is at a panel angle of 5 ° with the azimuth angle facing northeast (-45 °) with an output energy of 2365 MWh/year, specific production of 1564 kWh/kW/year, and normalized production of 4.29 kWh/kWp/day.